2006
DOI: 10.1177/1359105306065015
|View full text |Cite
|
Sign up to set email alerts
|

Peer Influences, Body-image Dissatisfaction, Eating Dysfunction and Self-esteem in Adolescent Girls

Abstract: A sample of 344 adolescent girls completed a variety of measures designed to index the associations among peer influences, body-image dissatisfaction, eating dysfunction and self-esteem. Results indicated that participants were significantly similar to their nominated friends on self-esteem, but not body image or eating disturbance. Peer measures were significantly associated with body dissatisfaction, eating problems and self-esteem. Peer suppression of feelings, internalization of the thin-ideal and appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
147
2
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(162 citation statements)
references
References 28 publications
6
147
2
7
Order By: Relevance
“…From this perspective, pathological eating behaviours (e.g., diet) may be seen as means to reach a body shape closer to the thinideal (Liimakka, 2014), thus averting feelings of inferiority. However, this strategy can become problematic; there is consistent evidence demonstrating that perceptions of inferiority based on physical appearance-focused social comparison are associated with maladaptive emotion regulation, anxiety and depressive symptoms, and specifically with body image dissatisfaction and eating psychopathology (Ferreira et al, 2013a;Pinto-Gouveia et al, 2014;Shroff and Thompson, 2006). Nonetheless, no studies to date examined whether one's social evaluations in comparison to others based on the body image domain are associated with QoL impairments.…”
mentioning
confidence: 99%
“…From this perspective, pathological eating behaviours (e.g., diet) may be seen as means to reach a body shape closer to the thinideal (Liimakka, 2014), thus averting feelings of inferiority. However, this strategy can become problematic; there is consistent evidence demonstrating that perceptions of inferiority based on physical appearance-focused social comparison are associated with maladaptive emotion regulation, anxiety and depressive symptoms, and specifically with body image dissatisfaction and eating psychopathology (Ferreira et al, 2013a;Pinto-Gouveia et al, 2014;Shroff and Thompson, 2006). Nonetheless, no studies to date examined whether one's social evaluations in comparison to others based on the body image domain are associated with QoL impairments.…”
mentioning
confidence: 99%
“…Moreover, at the collegiate level many relevant social systems (e.g., sororities, athletics) are drawn to peer-led programs because such programs serve a dual purpose of addressing an important issue (i.e., prevention of EDs) and creating leadership opportunities for students. Peers also may play a significant role in body image (Shroff & Thompson, 2006). Given that the above study is the only study to date to explore the delivery of an efficacious ED prevention program using PLs, replication appears important.…”
mentioning
confidence: 99%
“…When adolescent girls report that they are teased by their friends about their appearance, that their friends are preoccupied with weight and dieting, that they often have conversations about appearance with their friends, and that they see their friends as key influences on their ideas about weight loss and the perfect body, they are more likely to compare their own appearance to the appearance of others (Shroff and Thompson 2006b). In fact, Shroff and Thompson (2006b) found that higher levels of social comparisons help to explain the links between peer influence (i.e., peer teasing, preoccupation, conversations) and adolescent girls' body dissatisfaction. When adolescent girls individually report making more social comparisons, their body image concerns are higher; in addition, when friendship groups are characterized by having higher levels of social comparisons, friends in the group are more likely to be dissatisfied with their bodies ).…”
Section: Social Comparisonsmentioning
confidence: 96%